Phenotypic plasticity in leaf traits in response to experimental precipitation increase: wettability, foliar water uptake and gas exchange - Cavallaro, Agustín; Carbonell Silletta, Luisina; Askenazi, Javier Oscar; Goldstein, Guillermo; Bucci, Sandra Janet; Scholz, Fabian Gustavo (Wiley, 2023)
Water availability is one of the factors affecting plant growth and development, especially in arid and semiarid environments. Changes in precipitation due climate change alter water availability to plants impacting on plant physiology. Numerous studies have focused on plant response to reduced precipitation and less on the effects of increased precipitation. The main objective of this study was to evaluate biophysical and physiological leaf traits in response to experimental water addition in four dominant shrubs and one grass species in a Patagonian steppe, during the dry season. The experiment consisted of two treatments: control and water addition, increasing the average annual rainfall by 25% during 6 years. We measured leaf wettability, water status, transpiration, photosynthesis, stomatal conductance, water use efficiency and foliar water uptake (FWU). In addition, we determined the phenotypic plasticity index of these evaluated traits. We expected lower FWU and higher transpiration and photosynthesis rates due changes in leaf surface properties under water addition treatment. All study species responded significantly to treatment with higher loss of water per transpiration and lower FWU. Also, all species increased photosynthesis rate and water use efficiency (WUE). However, water potential and leaf wettability did not change with higher precipitation. Thus, higher phenotypic plasticity was observed in functional than in morphological traits. Since functional traits were more sensitive than leaf surface traits, plants may quickly take advantage when environmental conditions tend to be more favourable to growth. Our findings suggest that plants of Patagonian steppe have adaptive ability to respond to environmental changes through plastic responses.